BIOCHEMICAL PROFILE, BACTERIAL PROFILE, AND ANTIBIOTIC SUSCEPTIBILITY PATTERN OF THE ISOLATES OF NEONATAL SEPTICEMIA IN TERTIARY CARE HOSPITAL, VISAKHAPATNAM: Neonatal sepsis - GESHMANJALI, KAKARALA; SARISHMA, CHAPARALA; SAIKUMAR, BONELA; SUNEETHA, NANNAPANENI (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The objective of the study was to determine sensitivity, specificity, and predictive values of C-reactive protein (CRP), leukocyte count, platelet count, and blood culture as indicators of neonatal sepsis. Methods: This prospective study was conducted in the Department of Paediatrics, GITAM Institute of Medical sciences and Research, Visakhapatnam during January 2019 to December 2019. The institutional ethics committee had approved the study. Eighty clinically suspected cases of neonatal sepsis constituted material of study. All neonates who were clinically suspected sepsis, categorized into 0–72 h (early onset) or late onset (>3 days) sepsis based on day of presentation. Detailed history and clinical findings were recorded in the pro forma and screened with CRP and various hematological tests with predetermined cutoff values and at the same time blood culture was sent. Concerning a clinical scenario CSF, urine analysis, chest X-ray, and infective focus swabs were all taken. The length of treatment and time spent in the hospital were recorded. The death rate was calculated, and numerous risk variables were evaluated. Results: Intrapartum risk factors such as a prolonged rupture of membrane >24 h, a long labor, several filthy vaginal examinations (>3) before birth, and foul-smelling liquid were all linked to culture-proven newborn sepsis. Any of the two risk factors listed above was a good predictor of sepsis with a positive culture. Neonatal sepsis impacted a higher percentage of low birth weight and preterm babies. The sensitivity and negative predictive value of the I/T ratio and CRP were both high. The most prevalent isolates were Klebsiella species, followed by Staphylococcus aureus and Escherichia coli. While S. aureus was 80% sensitive to Cefotaxime and Amikacin, Klebsiella species and E. coli were only 20% sensitive. All were sensitive to Ofloxacin in range of 75-100%. Septicemia with multiorgan dysfunction was the most common mode of death with 100% risk of mortality. Conclusion: Intraparum risk factors are significantly with culture proven sepsis. All sepsis screening parameters used were statistically significantly associated with culture proven sepsis. I/T ratio and CRP were more sensitivity and had high negative predictive value. CRP can be used as an early and predictable screening test for diagnosing neonatal sepsis.